Antibacterial Activity of Lactoperoxidase from Sheep Colostrum - Joseph, P.V; Mathew, Jyothis; Jacob, Claramma; Haridas, M. (Asian Journal of Chemistry, 2010)
Various immune factors of colostrum have been reported to be associated with antibacterial activity. Therefore investigations were carried out with a view to examine the antibacterial action of the enzyme lactoperoxidase from the colostrum of sheep. The lactoperoxidase was purified from colostrum of sheep using ion exchange chromatography on C.M Sephadex C-50 and gel filtration chromatography on G-100 (Sigma). Purified lactoperoxidase was found to have antibacterial action against a number of disease causing bacteria.